Assessing the Antifouling Effectiveness of the Novel Organic Coating for Adherent Species in the Seawater of the coastal area of Ha Long City, Quang Ninh Province (Vietnam) - Nguyen, Xuan Thai; Dao, Phi Hung; Nguyen, Thuy Chinh; Nguyen, Anh Hiep; Pham, Minh Quan; Do, Huu Nghi; Do, Cong Thung; Nguyen, Van Quan; Thai, Hoang (Vietnam Journal of Marine Science and Technology, 2024)
This paper presents the results of a 12-month testing period in seawater at Vung Oan, Ha Long City marine area, Quang Ninh Province (Vietnam), assessing the fouling organism’s removal effectiveness of polysiloxane (PS)/Ag-Zn zeolite/Cu2O nanocomposite coatings. This experiment is a substantial base to evaluate impact of Ag-Zn/zeolite and Cu2O nanoparticles (NPs) on growth of bacteria and macro-fouling organisms compared to a control coating without the above additives. The results indicated that the coating loaded with Ag-Zn/zeolite and Cu2O NPs exhibited a lower bacterial count than the coating without biocide additives. Specifically, the bacterial count was 9.6 × 105 for the coating with biocide and 2 × 107 for the coating without biocide. Regarding macro-fouling species, the analysis and identification of organisms attached to the coating samples revealed the presence of three fouling species: Perna viridis, Balanus amphitrite, and Haliclona cinerea. Modiolus barbatus, Nereis sp., and Xanthidae were only observed on surface of the control samples, suggesting that Ag-Zn/zeolite and Cu2O NPs can impede the development of Modiolus barbatus, Nereis sp., and Xanthidae on the coating surface. Furthermore, the average weight of macro-fouling organisms on the coating containing Ag-Zn/zeolite and Cu2O NPs was significantly lower (90 g/sample) than that of the macro-fouling organisms on the control coating (333 g/sample). Notably, one of the three samples with the Ag-Zn/zeolite and Cu2O NPs had the lowest weight of macro-fouling organisms, measuring only 35 g. Based on these findings, it can be concluded that polysiloxane/Ag-Zn/zeolite/Cu2O nanocomposite coatings show promise as antifouling paints for marine work applications.